Melanoma in patients with GATA2 deficiency. (10th December 2017) - Nguyen, Jannett; Alexander, Tiffany; Jiang, Hong; Hill, Natasha; Abdullaev, Zied; Pack, Svetlana D.; Hsu, Amy P.; Holland, Steven M.; Hickstein, Dennis D.; Engels, Eric A.; Brownell, Isaac
Summary: GATA2 deficiency is a recently described genetic disorder affecting hematopoietic stem cells and is associated with immunodeficiency, hematologic malignancy, and various cutaneous pathologies including cutaneous tumors. To explore the incidence and clinical course of melanoma in patients with germline GATA2 deficiencies, we conducted a retrospective chart review of 71 such patients and identified two with invasive melanoma. One melanoma was diagnosed early because it was associated with pruritus due to a graft‐versus‐tumor effect following bone marrow transplantation. The other one, a lentigo maligna melanoma, was locally excised but progressed to widespread metastasis and death several years later. Our observations and published studies of melanoma biology suggest an association between decreased GATA2 expression and melanoma progression. These findings suggest that GATA2 deficient patients may have an increased risk of melanoma and should be observed closely for new or changing skin lesions.